Ag nanoparticles on mesoporous carbon support as cathode catalyst for anion exchange membrane fuel cell. (5th April 2023) - Linge, Jonas Mart; Erikson, Heiki; Mooste, Marek; Piirsoo, Helle-Mai; Kaljuvee, Tiit; Kikas, Arvo; Aruväli, Jaan; Kisand, Vambola; Tamm, Aile; Kannan, Arunachala M.; Tammeveski, Kaido
Abstract: Silver nanocatalyst (40 wt%) is deposited on commercial mesoporous carbon support material (Ag/C) using two different wet chemical methods, to obtain high electrochemically active surface area. The catalyst materials are characterized by scanning electron microscopy, X-ray photoelectron spectroscopy, X-ray diffraction, thermogravimetric analysis and are evaluated toward the oxygen reduction reaction (ORR) in alkaline media employing the rotating disk electrode method. It is worth noting that the Ag/C leads to oxygen reduction through a direct four-electron pathway in alkaline medium. The silver catalyst on mesoporous carbon exhibits relatively higher mass activity for ORR (38 A g −1 ) compared to that with Vulcan carbon (32 A g −1 ) at −0.2 V vs SCE at room temperature. Anion exchange membrane fuel cell shows maximum power density of 310 mW cm −2 with Ag/C cathode catalyst using H2 and O2 gases at 65% RH conditions at 65 °C. Graphical abstract: Image 1 Highlights: 40 wt% Ag/C catalysts were prepared onto novel mesoporous engineered carbon supports. ORR on the synthesized Ag-based catalyst materials follows a four-electron pathway. Mass activity for ORR on Ag/C catalysts surpassed that of Ag/VC. Peak power density of 310 mW cm −2 with Ag/C cathode was obtained in AEMFC test.